Understanding talent management for sports organizations - Evidence from an emerging country. Issue 11 (17th June 2022) - Hassan, Yusuf; Pandey, Jatin; Varkkey, Biju; Sethi, Deepa; Scullion, Hugh
Abstract: Talent Management (TM) has emerged as a key strategic issue for global organizations. Despite the growth of global sports entities, research on TM in this context is scarce. This paper addresses this research gap and investigates major challenges in TM faced by organizations in professional sports business and makes an increasingly significant contribution towards the global economy. The question of what constitutes 'talent' in sports and how it can be strategically managed is a matter of concern which expands the knowledge and understanding of Talent Management practices in a unique and rapidly developing sector. The current study explores the scope and boundaries of TM practices for professional sports entities in the context of emerging economies. The study uses case study approach to examine TM for the Nepal based Everest Premier League (EPL) The study draws on the Social Exchange Theory (SET) and Human Capital Theory (HCT) to understand talent management practices and demonstrates how differing natures of socio-economic exchange can be observed across actors and stages of TM in the business of sports.